(untitled) (Studia Prawnicze / The Legal Studies, 2002)
"Korzyści" konstytuujących pojęcie subsydium [w rozumieniu Kodeksu Subsydiów (porozumienie Światowej Organizacji Handlu (WTO) o subsydiach i środkach wyrównawczych] nie można wywodzić z tych decyzji inwestycyjnych podmiotów publicznych, które nie naruszają standardu rozsądnego inwestora rynkowego. The ‘benefits’ constituting the concept of a subsidy [within the meaning of the Subsidies Code (World Trade Organisation (WTO) Agreement on Subsidies and Countervailing Measures)] cannot be derived from those investment decisions of public entities that do not violate the reasonable market investor standard.